Sistema jurídico y naturaleza. Consideraciones sobre el derecho y la naturaleza - Foy Valencia, Pierre (2015)
From some reflections on the man (culture) nature relationship, the paper arrives at a set of more specific considerations about nature and the legal system. These will allow sustaining some of their legal expressions: natural resources heritage, commons, and ecosystem, among others. To conclude, the theme of nature as subject will be discussed, complementing the discussion with the topic of the legal system and animals.